Study of the profile of stroke in a tertiary-care hospital in the sub-Himalayan region in north India - Dhiraj Kapoor; Pankaj Gupta; Shyam Sundar; Rupinder Sharma; Ashish Dhiman; Vishnu Agarwal (Universiti Kebangsaan Malaysia, 2015)
Background: Rapid urbanization of rural areas is predicted to increase the incidence of risk factors for vascular events such as stroke among the ruralites. A different culture, beliefs, terrain, and climatic conditions of Himachal Pradesh may have an impact on the profile of stroke. Objectives: To study the profile and the various risk factors of stroke in the sub-Himalayan region of north India. Material and Methods: It was an observational cross-sectional study conducted at the Department of Medicine, R.P. Government Medical College, Kangra, Himachal Pradesh, for a duration of 12 months, from June 2012 to May 2013. Consecutive patients presenting to the hospital with signs and symptoms of stroke were included in the study. Detailed history and clinical examination was carried out in all patients. CT scan, routine blood examination, and lipid profile were evaluated in all patients. Results: Total number of patients who presented with stroke in a year was 374. It formed 4.0% of the total hospital admissions in medical wards. The mean age of stroke patients was 66.17±12.9 years. Of the total patients, 254 (67.9%) were males and 120 (32%) were females; 127 patients (33.9%) presented between 6 am and 12 pm. The majority of patients presented in winter months, from November to January. Average delay in the presentation to hospital was 29 h. Only 79 (21.1%) patients presented within 3 h. Among the patients, 342 (91.4%) belonged to rural area, 61.4% had an infarct, and 38.6% had intracerebral bleed. The most common symptoms reported were weakness in 276 (73%) followed by speech abnormality in 53%. Hypertension as a risk factor was found in 174 (46.5%); 155 patients (41.4%) were smokers; and diabetes was present in 61 patients (16.4%). Average cholesterol level was 176±54.99 mg/dl, and average triglyceride level was 339 mg/dl. Conclusions: The major strength in our study was the predominance of rural population. The state has witnessed an increase in the incidence of stroke. Elderly population is predominantly affected. Average delay in presentation was 29 h, which is substantially high. Majority of the events occurred in winter months.